A cobalt(ii)heteroarylalkenolate precursor for homogeneous Co3O4 coatings by atomic layer deposition. Issue 38 (21st September 2017) - Büyükyazi, Mehtap; Fischer, Thomas; Yu, Penmgei; Coll, Mariona; Mathur, Sanjay
Abstract : We present a robust approach to prepare conformal Co3 O4 nanocoatings on high aspect ratio structures from a new cobalt metalorganic complex. Abstract : We present a new and efficient cobalt precursor, Co II (DMOCHCOCF3 )2, to prepare Co3 O4 thin films and conformal coatings. In the synthesis of this Co complex, heteroaryl moieties and CF3 -groups were combined leading to the precursor with high thermal stability and volatility. The suitability of this precursor for ALD deposition was tested on flat silicon substrates and TiO2 /C nanofibers upon process optimization. Deposition at 200 °C results in homogeneous and smooth Co3 O4 thin films with a growth rate of 0.02 nm per cycle. Conformal coatings have been successfully obtained on TiO2 /C nanofibers, making them an attractive platform for surface chemistry studies on high aspect ratio structures for future photocatalysts, sensors, supercapacitors and batteries.